2022
DOI: 10.3389/fevo.2022.971534
|View full text |Cite
|
Sign up to set email alerts
|

Study on the synergistic effect of foreign trade, technological progress, and carbon emissions

Abstract: A primary development plan for a country is to attain carbon neutrality and high-quality international commerce development. This study uses panel data from 30 provinces in mainland China to analyze the dynamic interplay between international trade, technological innovation, and carbon emissions. The findings show that foreign trade, technological progress, and carbon emissions all have their own “economic inertia” that can be self-motivated and self-reinforcing. Foreign commerce and carbon emissions are mutua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Scholars mainly use Kaya identity (Ma and Cai, 2018;Eskander and Nitschke, 2021), Divisia index method (Ma and Cai, 2018;Eskander and Nitschke, 2021), and Laspeyres index decomposition method (González and Martínez, 2012;Chen et al, 2021) decompose the influencing factors of carbon emissions. Although the conclusions of different methods are different, it is generally believed that technological innovation (Zhang G. et al, 2022), energy structure (Pui and Othman, 2019), industrial structure (Han and Jiang, 2022), and economic growth (Xiao and Peng, 2023) are the main factors affecting carbon emissions.…”
Section: Digital Economy Development and Carbon Emission Intensitymentioning
confidence: 99%
“…Scholars mainly use Kaya identity (Ma and Cai, 2018;Eskander and Nitschke, 2021), Divisia index method (Ma and Cai, 2018;Eskander and Nitschke, 2021), and Laspeyres index decomposition method (González and Martínez, 2012;Chen et al, 2021) decompose the influencing factors of carbon emissions. Although the conclusions of different methods are different, it is generally believed that technological innovation (Zhang G. et al, 2022), energy structure (Pui and Othman, 2019), industrial structure (Han and Jiang, 2022), and economic growth (Xiao and Peng, 2023) are the main factors affecting carbon emissions.…”
Section: Digital Economy Development and Carbon Emission Intensitymentioning
confidence: 99%
“…Finally, most studies neglected the impact of reducing carbon emissions on trade while concentrating primarily on the one-way effect of foreign trade on carbon emissions. In the last article, Zhang et al (2022) examined the dynamic interactions between global business, technological innovation and carbon emissions via the panel vector autoregressive model. They demonstrated that whereas international trade and carbon emissions were mutually hindering, technological advancement and improving carbon emissions mutually supported each other.…”
Section: Digital Technology and Carbon Neutralitymentioning
confidence: 99%
“…Under the constraints of the twin carbon targets of carbon peaking and carbon neutrality, it is essential to study how to achieve a reduction in corporate carbon emissions. Zhang et al (2022) argue that the responsibility for carbon emissions lies with firms rather than consumers. In terms of supply and demand theory, the price of carbon depends on the government's supply of carbon credits and firms' demand for carbon credits.…”
Section: Introductionmentioning
confidence: 99%